A randomized controlled trial comparing the management of incomplete abortion with oral 600 mg misoprostol with manual vacuum aspiration (MVA) - Niramaya Madhual; Heena Dixit Tiwari; Susmita Das; Saloni Kamboj; Smit Thakkar; Hala Kashif; Akriti Mahajan (Journal of Pharmacy and Bioallied Sciences, 2024)
Introduction: In the first trimester, almost one in five identified pregnancies end in spontaneous miscarriage, and another 22% result in induced abortion. After a spontaneous and/or induced abortion, there may be retained products of conception (POC). Because of its relatively poor efficacy and the unpredictability of the time interval until spontaneous evacuation, expectant treatment is not often chosen by healthcare professionals. In view of these facts, the current study's objective was to weigh the effectiveness of MVA and oral misoprostol 600 mg in managing incomplete abortion. Materials and Procedures: The investigation was conducted at the tertiary care center in India. The survey was conducted for one year. Subjects were selected from those attending the department for either spontaneous or induced abortions. A total of 230 women were randomly assigned to receive the interventions of a single dose of oral misoprostol 600 mcg or MVA. They were equally distributed to two groups and observed for the various parameters of success, signs and symptoms, satisfaction, and complications. The obtained values were compared statistically for the significance at <0.05 of P values. Results: Of the 200 subjects (30 lost to follow-up), there was no significant variance in the demographics, clinical outcomes, and complications between the groups. However, the pain, fever, shivering, and satisfaction parameters were statistically variant between the groups. Fever, shivering, and pain were lower for the MISO subjects while satisfaction was reported higher from subjects in MISO group. Conclusion: MISO and MVA are acceptable, safe, and efficient therapies for first-trimester un-complicated incomplete abortion. Nonetheless, misoprostol appears to be a marginally superior option to MVA in terms of accessibility, low therapy costs, reduced pain, and reduced demand for specialized personnel or equipment.